Steryl ferulates composition in twenty-two millet samples: Do "microwave popping" and fermentation affect their content?. (15th October 2022) - Balli, Diletta; Cecchi, Lorenzo; Pieraccini, Giuseppe; Palchetti, Enrico; Innocenti, Marzia; Mulinacci, Nadia
Highlights: Different steryl ferulates composition were found in different millet genera. Campestanyl and sitostanyl ferulates were the most abundant steryl ferulates. Pearl, finger and foxtail millet samples showed the highest steryl ferulates content. "Popping" increased steryl ferulates by the 50% compared to the untreated sample. Fermentation increased steryl ferulates five times compared to the untreated sample. Abstract: Climate change has led to rediscovery of minor drought tolerant grains such as millet. Among its bioactive molecules, steryl ferulates have been poorly explored. Steryl ferulates composition of was investigated by high performance liquid chromatography-diode array detector-tandem mass spectrometry and high resolution tandem mass spectrometry in twenty-two millet samples and also in some fermented and microwave heated samples. Six compounds were found in Panicum, Pennisetum, Eleusine and Setaria genera, with a prevalence of campestanyl and sitostanyl ferulate. The lowest steryl ferulates content was found in Panicum, with values ranging from 2.98 ± 0.04 µg/g to 8.72 ± 0.41 µg/g. Foxtail millet and finger millet showed the highest amount with 46.07 ± 5.20 µg/g and 85.29 ± 4.30 µg/g, respectively. As for pearl millet, microwave heating and fermentation increased steryl ferulates by two (33.77 ± 0.88 µg/g) and five (75.83 ± 1.25 µg/g) times, with respect to the untreated sample. Microwave heating and fermentation could be used to increase steryl ferulates in millet.